A Decade of Antibiotic Resistance in E. Coli in Urinary Tract Infections : A Study from a Tertiary Care Hospital in Bangladesh - Islam Majumder, Md Mahabubul; Rahaman Mahadi, Ashrafur; Ahmed, Tareq; Sakib, Nazmus; Ahmed, Mostaque; Nazim Uddin, Mohammad; Mohammad Shihab, Hossain (Medicine Today, 2025)
Introduction: This study aimed to discern evolving bacteriology and antibiotic resistance trends of E.coli among uropathogens, contrasting with a previous study. Materials and Methods: This study was conducted at Cumilla Medical College Hospital, Bangladesh, between June 2011 and June 2021, it encompassed three phases: 2011, 2016, and 2021, with participant counts of 551, 658, and 2312, respectively. Notably, females exhibited higher UTI prevalence. Results: Urine samples, 551 (2011), 658 (2016), and 2312 (2021), were cultivated for E. coli resistance assessment. Predominantly, females (18-40 years old, rural, married, sexually active, middle-income) exhibited symptoms like dysuria, fever, urgency, and abdominal pain. In 2021, UTI prevalence was higher in females (32.06%) than males (22.86%). E. coli dominated isolates, constituting 61.6% (2021), 86.0% (2016), and 75.5% (2011). Antibiotic susceptibility tests on 410 E. coli isolates from 2021 unveiled high resistance to cephalosporins (61.75-83.33%), fluoroquinolones (43.36-51.72%), macrolides (89.49%), cotrimoxazole (52.79%), and nitrofurantoin (25.38%). Resistance rates were lower for carbapenems (1.47-3.92%), aminoglycosides (5.91-20.79%), and piperacillin/tazobactam (11.55%). Comparing the three phases highlighted escalating E. coli resistance from 2011 to 2021: imipenem (0 to 4.2%, p=0.007), meropenem (2.0 to 3.4%, p=0.021), amikacin (2.0 to 6.2%, p=0.017), gentamicin (14.0 to 23.7%, p=0.043), and nitrofurantoin (9.0 to 31.2%, p=0.002). Amoxicillin/clavulanic acid resistance decreased (24.0 to 17.4%, p=0.036). Conclusion: In summary, this study illuminated burgeoning E. coli resistance in UTIs, notably against common oral antibiotics. The findings underscore the indispensability of urine culture and susceptibility tests in steering appropriate empirical antibiotic therapies. Medicine Today 2025, Vol.37 (1): 44-51